Design and handling dynamic analysis of electric vehicle chassis with yaw direction oscillatable battery pack. Issue 3 (4th March 2022) - Tian, Mengjian; Hu, Qiyuan; Gao, Bingzhao; Ding, Haitao; Chen, Hong
Abstract : As the energy storage device of an electric vehicle (EV), in order to meet the mileage requirements, a battery pack always has large volume and mass and is responsible for a considerable portion of the yaw rotational inertia of the entire vehicle. As the yaw rotational inertia has a negative impact on the vehicle cornering response, a new type of EV chassis structure is proposed herein, which is equipped with a yaw direction oscillatable battery pack. This battery pack can reduce the yaw rotational inertia of the vehicle to improve handling performance while meeting the mileage and spatial layout requirements. Based on this chassis structure, a linear 3-degrees-of-freedom (DOF) mathematical dynamic model and an ADAMS multi-body dynamics model are built. Then, the lateral dynamic characteristics are estimated for different typical test conditions by simulation. The comparative results and analysis between the new type of chassis and the conventional chassis are presented. The new type of chassis is shown to have advantages in terms of handling performance.